Avaliação das propriedades psicométricas do questionário disabilities of the arm shoulder, and hand (DASH) em indivíduos com sintomas de impacto no ombro – análise rasch e classificação internacional de funcionalidade - Almeida, Rafaela Firmino de (2020)
Introduction: Patients with shoulder impingement symptoms present affected the quality of life and upper limb function. The Disabilities of the Arm Shoulder and Hand (DASH) questionnaire is widely used to assess pain and function in these patients. However, no study has evaluated the psychometric properties of DASH in individuals with shoulder impingement symptoms and related the level of difficulty of the items with the descriptors of the International Classification of Functionality (ICF). Objectives: To evaluate the psychometric properties of the DASH questionnaire applied in individuals with shoulder impingement symptoms and to describe which ICF domains are influenced by the shoulder impingement symptoms based on the DASH questionnaire. Methods: Three hundred and ten individuals participated in this study of both sexes, aged over 18 years, who presented symptoms of impact on the shoulder. All participants underwent screening to assess the inclusion and exclusion criteria of the study. Individuals who met the eligibility criteria were assessed using personal aspects (age and sex) and body function (dominance of the affected side, chronicity of symptoms, and the onset of pain during arm elevation). The Brazilian version of the DASH questionnaire was used to assess pain and the function of individuals' upper limbs. Responses were assessed using the Rasch model. After analysis, the ranking of the results was correlated with the ICF. Results: The DASH questionnaire showed reproducibility of 0.93 and internal consistency of 0.95, demonstrated by the Intraclass Correlation Index and Cronbach's alpha, respectively. The item considered most difficult was 25 ("Arm, shoulder or hand pain when you performed any specific activity") and the easiest item 3 ("Turn a key"). Thirty-nine percent (n = 27) of the subgroup of 69 in individuals with shoulder impingement symptoms had maximum item scores. Item 15 ("Put on a pullover sweater") showed differential functioning by age, item 11 ("Carry a heavy object - over 10 lbs") by sex. Seven items showed differential functioning by the onset of pain during arm elevation . The most difficult items in the DASH questionnaire covered the domain "Body function" of the ICF. Conclusion: Although some psychometric properties of the DASH questionnaire are adequate by the Rasch model to assess individuals with shoulder impingement symptoms, adjustments are necessary for some items. Clinicians should exercise caution when interpreting the results, especially in patients with an onset of pain during arm elevation above 120º.